Literature Review: Factors Influencing Purchasing Decisions in the Service Industry - Umpusinga, Hasrun Afandi; Warganegara, Tri Lestira Putri; Alam, Iskandar Ali; Habiburrahman, Habiburrahman; Barusman, Andala Rama Putra (Islamic Economics Journal, 2024)
This research focuses on the factors that interact with each other and influence consumers' purchasing decisions, as well as how implementing effective marketing strategies can influence these decisions across various industry sectors. The purpose of the study is to examine studies that are relevant to purchase decisions, this study uses a qualitative method with a systematic literature study approach, which is an assessment and analysis of previous research related to purchase decisions, using the keywords "Purchase Decision" and "Travel" in the period from 2004 to 2024 (20 years). The results of the study found that purchasing decisions are influenced by cognitive dissonance, social influence, corporate alliances, brand equity, brand preferences, gender roles: female dominance, online forum browsing, price, online reviews, promotions, demographics, travel preferences, domestic family decisions, brand decisions, price decisions, circle of acquaintance decisions, compromises, temporal constructions, perceived ease of use, electronic word of mouth, content marketing,  Brand image, lifestyle, trust in tour packages, trust in payment methods, intention to purchase tour services, promotion of online tour services, place of residence, previous purchase experience, information sources used and perception of reliability, professional status, age, education level, financial situation, and perception of value.